AN ANALYSIS OF THE MANUFACTURING POSSIBILITY OF SPECIAL ANKLE FOOT ORTHOSIS COMPONENTS BY OMPARISON BETWEEN THE REQUIRED PRECISION AND THE VAILABLE PRECISION ON A VERTICAL MACHINING CENTER PROGRAMED WITH TOPSOLID - Alexandru STANIMIR; Florin RUSU; Cosmin BERCEANU; Dumitru FILIP (Fiabilitate şi Durabilitate)
Validation of different solutions adopted to achieve new ankle foot orthosis involves among others their prototyping. In these paper we developed a representative part for two axis machining that requires the use of the main features of TopSolid Cad and Cam modules, and that assumes the use of the main manufacturing processes that usually may be met on a vertical machining center. Also, in order to determine the dimensional and geometrical deviations of the part this was done on the YMC 1050 machining center. After comparing the measured deviations with the requirements of various components of orthesis, we concluded that the available precision meets the requirements and that the machining center with TopSolid software that we have will enable us to realize special ankle foot orthosis of quality, for experimental research .